2019
DOI: 10.3899/jrheum.180574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Timing and Duration of Statin Exposure on Risk of Hip or Knee Revision Arthroplasty: A Population-based Cohort Study

Abstract: Objectives.To determine whether the timing and duration of statin exposure following total hip/knee arthroplasty (THA/TKA) influence the risk of revision arthroplasty.Methods.Subjects from the Clinical Practice Research Datalink, a large population-based clinical database, who had THA/TKA from 1988 to 2016, were included. Propensity score adjusted Cox regression models were used to determine the association between statin exposure and the risk of revision THA/TKA, (1) at any time, and (2) if first exposed 0–1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…When a patient first comes to the emergency room, it is pertinent that the physician acquires a history about his or her comorbidities, chronic medications, trauma and whether or not he or she has suffered from pain associated with the joint before fracture occurred. This is critical as it may suggest that there was a pre-existing aseptic loosening of the implant, possibly due to component loosening, polyethylene wear with osteolysis, ligamentous laxity, arthrofibrosis or patellofemoral complications [28]. Loosening due to infection could occur as well, and begins with a history of pain, swelling, erythema and prolonged wound drainage or a sinus tract [29].…”
Section: Evaluation and Analysismentioning
confidence: 99%
“…When a patient first comes to the emergency room, it is pertinent that the physician acquires a history about his or her comorbidities, chronic medications, trauma and whether or not he or she has suffered from pain associated with the joint before fracture occurred. This is critical as it may suggest that there was a pre-existing aseptic loosening of the implant, possibly due to component loosening, polyethylene wear with osteolysis, ligamentous laxity, arthrofibrosis or patellofemoral complications [28]. Loosening due to infection could occur as well, and begins with a history of pain, swelling, erythema and prolonged wound drainage or a sinus tract [29].…”
Section: Evaluation and Analysismentioning
confidence: 99%
“…There was a small protective effect of exposure to statins > 5 years following primary surgery, though the confidence intervals included unity. Compared to participants exposed to statins for a total duration of less than one year, exposure for 1-2, 2-3, 3-4, and 4-5 years did not appear to be associated with THA/TKA revision risk, though exposure for a total duration of >5 years was associated with a reduced hazard ratio for revision, 0.74 (0.62, 0.88) 62 .…”
Section: Pharmacoepidemiologic Evidence Of a Role For Statins In Arthmentioning
confidence: 76%
“…Lalmohamed et al demonstrated that depending on the epidemiological study design used there can be significant differences calculated in incidence ratio of revision surgery. A more recent analysis using CPRD data sought to further investigate association between statins exposure and risk of revision following THA/TKA and also the impact of duration and timing of statin exposure on revision risk, using propensity score adjusted Cox models 62 .…”
Section: Pharmacoepidemiologic Evidence Of a Role For Statins In Arthmentioning
confidence: 99%
“…No statistically significant effect of statin exposure on revision risk >5 years following primary surgery was observed. Compared to participants exposed to statins for a total duration of less than one year, exposure for 1-2, 2-3, 3-4, and 4-5 years did not appear to be associated with THA/TKA revision risk, though exposure for a total duration of >5 years was associated with a reduced hazard ratio for revision surgery, (HR (95%CI) 0.74 (0.62, 0.88) 60 . The data from these studies demonstrate a small but significant effect of statins on reducing the risk of revision arthroplasty.…”
Section: Pharmacoepidemiologic Evidence Of a Role For Statins In Arthmentioning
confidence: 88%
“…Using data from both cohorts, statin exposure was associated with a small though significant reduction in risk of revision (incident rate ratio=0.9; 95% CI, 0.89, 0.96). A more recent analysis using CPRD data looked at impact of duration and timing of statin exposure on revision risk 60 . Of those exposed to statins following THA/TKA, 852 (1.3%) had revision arthroplasty, compared to 2,648 (3.1%) of those unexposed; adjusted hazard ratio for revision in those exposed vs those unexposed, 0.82 (0.75, 0.90).…”
Section: Pharmacoepidemiologic Evidence Of a Role For Statins In Arthmentioning
confidence: 99%